Censorship and economic film in Zimbabwe - Rwafa, Urther (Unisa Press, 2016)
This article explores the link between censorship and films on economic issues in Zimbabwe. Zimbabwean nationalist discourses monopolise the land as the only theme that authorities feel constitute an important subject for film or artistic expression. This is a form of censorship. However, the films also undermine this assumption that put salience on the land issue only. The films do so clandestinely, first circulating in circuits where censoring discourses of public officials are not able to patrol at all times and, second, through informed debates by academics and intellectuals discussing issues that range from democracy, corruption, land and women’s role.